Pendampingan Kelompok Kategorial Dalam Pelaksanaan Weekend Pastoral Di Paroki St. Vincensius A Paulo Malang - Wiwin Wiwin; Bernadeta Sri Jumilah (Jurnal Pelayanan Pastoral, 2020)
Pastoral Weekend is an activity of STP-IPI Malang students as a form of community service which is run from Saturday to Sunday. Students run Pastoral Weekend in the parish area of St. Vinsensius Malang by actively involving himself in categorical groups in the environment. In the neighborhoods, categorical groups based on age have been formed with different kinds of activities. The presence of students in categorical groups is expected to contribute to the development of faith for the people. This research is based on the basic community development theories which are used as the basis for the development of the ummah, how the shepherding of the people in basic communities is carried out. This study aims to explore categorical groups and their activities in which students are involved in activities in each of these groups. The involvement of students in this activity is expected to be a means of learning in applying material in lectures and coaching as prospective pastoral servants. The method used in this research is a qualitative method which tries to explore a process, namely the weekend pastoral of pastoral care study program students in basic communities (wards) specifically in St. Parish. Vincent de Paul. The results showed that the involvement of students in 9 environments made a positive contribution to the categorical groups, especially the Happy Week group.